WEED INTERFERENCE PERIODS IN PRE-SPROUTED SUGARCANE SEEDLINGS - Amaral, F. C. R.; Nepomuceno, M. P. [UNESP]; Chaves, A. R. C. S.; Carlin, S. D.; Azania, C. A. M. (Univ Federal Vicosa, 2019)
The aim of this research was to determine weed interference periods in sugarcane cultivated under the system of pre-sprouted seedlings, taking into account the impact on the final plant stand, and bud yield and stalk yield. In the field, this study used a randomized block design with 14 treatments and four replications. The treatments consisted of periods of control and weed coexistence with the sugarcane crop (cultivar IACSP95-5000): 30, 60, 90, 120, 150, 180, 210 and 240 days after planting. A phytosociological survey was carried out in the experimental area, and the species Merremia aegyptia, Urochloa decumbens and Nicandra physaloides were found to be predominant. At the end of 240 days, regression analysis was performed according to Boltzmann's sigmoidal model and considering loss tolerance of 5% in the evaluated variables. For final plant stand, the period prior to interference was 31 days and the total period of interference prevention was 187 days. For bud yield, the period prior to interference was 23 days and the total period of interference prevention was 178 days. For stalk yield, the period prior to interference was 19 days and the total period of interference prevention was 195 days. Weed interference was detrimental to all evaluated variables, with losses of up to 100% of the sugarcane plants after 120 days of weed coexistence.
Keywords: Merremia aegyptia; Urochloa decumbens; weed competition; critical periods; PSS; Saccharum spp.